The Influence of Work Environment and Workload on Job Satisfaction and its Impact on Employee Loyalty - Usniarti, Juli; Nuvriasari, Audita (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study was to analyze the effect of work environment and workload on job satisfaction and its impact on employee loyalty of PT Erhsali Mitra Investama. The research sample was 44 employees. The data analysis technique uses SEM with smartPLS 4.0 software. The results of the study prove that: (1) Environment has no significant effect on employee loyalty, (2) Work environment has a positive and significant effect on job satisfaction, (3) Workload has no significant effect on employee loyalty, (4) Workload has a positive and significant effect on employee job satisfaction, (5) Job satisfaction has a positive and significant effect on employee loyalty, (6) Job satisfaction significantly mediates the effect of work environment on employee loyalty, (7) Job satisfaction does not significantly mediate the effect of workload on employee loyalty. The results showed that job satisfaction has a significant influence on employee loyalty. However, through the mediation test, it was found that job satisfaction does not serve as a significant mediator in the relationship.